Kecerdasan Emosional dan Kepemimpinan Kepala Madrasah dalam Aplikasi Penguatan Pendidikan Karakter (PPK) di Madrasah - Nuryati Djihadah (Jurnal Pendidikan Madrasah, 2020)
The research aims to describe the positive correlation of emotional intelligence and the effectiveness of head of madrasah in character education reinforcement application (PPK) in the madrasah. The study uses literature study methods on journals and relevant books. The results of this study explained that the emotional intelligence and the effectiveness of the head of madrasah leadership became a very important factor in the success of applying character education reinforcement in the madrasah. The implications, from this study revealed that to apply PPK in madrasah, the head of the madrasah need to improve leadership effectiveness and emotional intelligence. This effort is important in line with the institution's efforts to apply the increase in PPK in madrasah. The effort must be clear and objective to be used as a guideline in order to improve the quality of a great, strong and dignified madrasah.